1981
DOI: 10.1111/j.1365-2621.1981.tb03049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking Rates in Electric or Microwave Oven on Cooking Losses and Retention of Thiamin in Broilers

Abstract: A study was conducted to determine the effect of two microwave oven and two electric oven cooking rates on retention of thiamin and cooking losses with broiler chickens. Thiamin was determined by a microbiological turbidimetric assay of raw and cooked meats. Broilers cooked in the microwave oven retained more thiamin than broilers cooked in the electric oven. There was no difference in thiamin retention between broilers cooked in the microwave oven at 800 and 1600 watts. Broilers cooked in the electric oven at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
1
5
1
Order By: Relevance
“…This retention value of 61% in whole chicken and 64% in cooked separable lean of chicken was comparable to the retention of 63.5% reported by Al- Khalifa and Dawood (1993) in microwave cooked dark muscles of chicken. The trend of a higher retention of thiamin in microwave-cooked meat than conventionally cooked ones was also reported by Hall and Lin (1981), AlKhalifa and Dawood (1993) and Uherova et al (1993).…”
Section: Thiaminsupporting
confidence: 70%
See 1 more Smart Citation
“…This retention value of 61% in whole chicken and 64% in cooked separable lean of chicken was comparable to the retention of 63.5% reported by Al- Khalifa and Dawood (1993) in microwave cooked dark muscles of chicken. The trend of a higher retention of thiamin in microwave-cooked meat than conventionally cooked ones was also reported by Hall and Lin (1981), AlKhalifa and Dawood (1993) and Uherova et al (1993).…”
Section: Thiaminsupporting
confidence: 70%
“…Since then there has been continuous research on the retention of vitamins on different types of cooking. Some of these studies include work by Ang et al (1975), Benterud (1977), Hall and Lin (1981), Warthesen et al (1984), Bertelsen et al (1988), Nagra and Khan (1988), RummKreuter and Demmel (1990), El-Shimi (1992), Al-Khalifa and Dawood (1993), Uherova et al (1993), Hill (1994), Selman (1994), Ryley and Kajda (1994) and Rahmani and Muller (1996). Abbreviations: e/oven: earth-oven; HPLC: high performance liquid chromatograph; L/chops: lamb chops; m/wave: microwave; na: not analyzed; o/roast: oven roast Although conservation of nutrients is a major consumer concern related to food preparation, there has not been any research conducted to study the retention of nutrients in foods cooked in an earth-oven, which is a very popular traditional food preparation method in the Pacific Islands.…”
Section: Introductionmentioning
confidence: 98%
“…Their results are in line with those of Cooksey et al (1990) observed during roasting. Results of thiamin losses in chicken meat are in line with those of Hall and Lin (1981), Barbeau and Schnepf (1989), and Ang et al (1978), in contrast to Al-Khalifa and Dawood (1993), who observed a retention of thiamin of only 45% during roasting. Bogna´r (1984) reported losses of thiamin in various conditions of heat treatment of meat in the range of 9-70%.…”
Section: Thiamincontrasting
confidence: 51%
“…The fresh carcasses and roasted samples were assayed for vitamins B , , B, and niacin contents using the procedures described by AOAC ( 1984) while observing suitable precautions to ensure reliability of data (Bowers et al 1974;Ang et al 1978;Korschgen and Baldwin 1978;Hall and Lin 1981). The moisture content of the meat samples was determined by drying each sample in a vacuum oven at a temperature and pressure of 90°C and 130 mbar, respectively, until a constant weight was attained.…”
Section: Methodsmentioning
confidence: 99%